Faktor Ekonomi yang Mempengaruhi Penyerapan Tenaga Kerja di Indonesia: Economic Factors Affecting Labor Absorption in Indonesia - Linda Rahmawati; Alifa Ulfiyyati; Indri Juliyani Putri (JEMeS - Jurnal Ekonomi Manajemen dan Sosial, 2025)
This study aims to examine the effect of economic growth, investment, and the number of wage earners on employment absorption in Indonesia. The research utilizes time series data obtained from the World Bank for the period 1960–2023. The analytical method employed is multiple linear regression. The results indicate that the number of wage earners has a significant positive impact on employment absorption. In contrast, the variables of economic growth and investment show a negative but insignificant influence. This suggests that despite increases in economic growth and investment, both have yet to produce a meaningful effect on job creation, which may be attributed to the dominance of capital-intensive sectors. These findings are important as input for the formulation of labor market policies in Indonesia.